Energy-efficient, application-aware medium access for sensor networks - Rajendran, V.; Garcia-Luna-Aveces, J.J.; Obraczka, K. (IEEE International Conference on Mobile Adhoc and Sensor Systems Conference, 2005, 2005)
We introduce FLAMA (flow-aware medium access), an energy-efficient medium-access control (MAC) protocol designed for wireless sensor networks. FLAMA achieves energy efficiency by preventing idle listening, data collisions and transmissions to a node that is not ready to receive packets. It adapts medium access schedules to the traffic flows exhibited by the application. FLAMA is simple enough so that it can be run by nodes with limited processing, memory, communication, and power capabilities. We evaluate the performance of FLAMA through simulations and test-bed experimentation. Simulation results indicate that, in terms of reliability, queuing delay and energy savings, FLAMA outperforms TRAMA, the first traffic-adaptive, schedule-based MAC proposed for sensor networks, and S-MAC, a contention-based energy-efficient MAC. FLAMA achieves significantly smaller delays (up to 75 times) when compared to TRAMA with significant improvement in energy savings and reliability, demonstrating the importance of application awareness in medium access scheduling. Our simulation and test-bed results show that FLAMA achieves better end-to-end reliability with significant energy savings compared to S-MAC